Does internet use promote the health of empty-nest older adults in rural China? The mediating role of social participation using a propensity score matching approach - Li Shen; Yawen Zheng; Mengting Wang; Hong Pan; Wenqian Jian; Xudong Yang; Xudong Yang; Wei Wang; Li Chen (Frontiers Media S.A., 2024)
BackgroundThe rapid growth of internet use among older adults in rural China offers a unique opportunity to examine its potential impact on their health. This study seeks to explore the relationship between internet use and the emotional, physical, and cognitive health of empty-nest older adults in rural China, while also considering the mediating role of social participation in this relationship.MethodsA total of 3,478 empty-nest older adults were selected from the China Health and Retirement Longitudinal Survey (CHARLS) in 2020. Among them, 820 individuals were included in the study using a propensity score matching (PSM) method to reduce the impact of selection bias. The participants' depression, physical health, and cognitive health were measured using the Center for Epidemiological Studies Depression Scale (CES-D), the Activities of Daily Living (ADL) scale, and a composite cognition score, respectively. Social participation was assessed based on engagement in various activities over the past month.ResultsAfter controlling for confounding factors through PSM, it was found that older adults who used the internet exhibited significantly lower level of depression and higher physical health compared to older adults who did not use the internet. However, there was no significant difference in cognitive health between the two groups. The mediating effect analysis revealed that social participation partially mediated the relationship between internet use and physical health, but not emotional health.ConclusionThe study suggests that internet use can improve emotional and physical health of older adults living in rural China without children at home, with social participation being a mediator in the relationship between internet use and physical health. Future research should explore the underlying mechanisms and develop targeted interventions to promote internet use and social engagement in this population.